The Effects of in Cigarette Excise Increase Policies, Price, and Income on People’s Cigarette Consumption - Aqmarina, Nadhilah Dwi; Aminullah Achmad Muttaqin (Islamic Economics and finance in Focus, 2025)
The ministry has issued the latest PMK Number 191/PMK.010/2022 on tobacco excise rates. One of the reasons for the government to increase excise rates on tobacco products is to reduce the level of public consumption of cigarettes. The purpose of this study is to determine the effect of excise tax increases, prices and income on cigarette consumption in Malang City. The variables used are cigarette consumption as the dependent variable, cigarette excise tax increase, and price as the independent variable, and income as the control variable. The research method used is descriptive analysis using primary data. Primary data was obtained from distributing questionnaires. The results showed that the increase in excise tax, price, and income had a significant effect on cigarette consumption in Malang City.